Improving Students' Learning Outcomes To Read And Write With Early Bird Media In English Learning At State 3 Ropoh Elementary School - Uud Aisyah (Prosiding University Research Colloquium, 2021)
EARLY BIRD is a medium that is used in Elementary School (SD) Negeri 3 Ropoh toteach English to students. This medium is used to teach and assess the reading skills ofelementary school children (SD) in Negeri 3 Ropoh in understanding English languageand the teachers' inventiveness. English instructors who are members of the EnglishTeacher Working Group (SD) Negeri 3 Ropoh have been introduced to this material.Based on the Early Bird operating principle, this media can assist English teachers indeveloping alternative learning media. Early Bird isn't just a learning tool; it's also a wayof life, However, it may motivate instructors to design alternative English learningmaterial as part of the English teaching and learning process at (SD) Negeri 3 Ropoh.